2017
DOI: 10.1039/c7sc02719b
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthetic prion protein (PrP) variants carrying glycan mimics at position 181 and 197 do not form fibrils

Abstract: Semisynthesis and characterization of homogeneously mono- and di-PEGylated full length PrP variants to study the impact of PEGylation (as N-glycan mimics) on protein folding and aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 53 publications
3
24
0
1
Order By: Relevance
“…Thus, lipopeptides can be used as mimics of the GPI anchor's ability to attach PrP to the cell membrane. A similar strategy with regard to using a lipidated peptide as a GPI‐mimicking membrane anchor was pursued by Becker et al, when starting to develop semisynthetic strategies, based on EPL and protein trans ‐splicing (PTS) (Figure ), to access to different posttranslationally modified PrP variants (Figure ) …”
Section: Semisynthesis Strategies For Prpmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, lipopeptides can be used as mimics of the GPI anchor's ability to attach PrP to the cell membrane. A similar strategy with regard to using a lipidated peptide as a GPI‐mimicking membrane anchor was pursued by Becker et al, when starting to develop semisynthetic strategies, based on EPL and protein trans ‐splicing (PTS) (Figure ), to access to different posttranslationally modified PrP variants (Figure ) …”
Section: Semisynthesis Strategies For Prpmentioning
confidence: 99%
“…This strategy was aimed at introduction sugars into PrP but did not fully succeed. Shortly after that, Araman et al demonstrated a semisynthetic approach to generate PrP variants modified with monodisperse PEG chains as mimics of N ‐glycans that are similar in size and molar mass (Figure C). A new EPL strategy was established to achieve this, in which expressed PrP (aa 23‐177) with a C ‐terminal thioester is used in EPL reactions with PEGylated, synthetic peptides (aa 179‐231).…”
Section: Semisynthesis Strategies For Prpmentioning
confidence: 99%
See 1 more Smart Citation
“…Christian Becker (University of Vienna, Austria) discussed a semisynthetic approach to generate prion protein (PrP) variants modified with monodisperse poly(ethylene glycol) (PEG) units as mimics of N‐glycans. The incorporation of PEG at different glycosylation sites in PrP only induced small changes in the secondary structure, but effectively inhibited the aggregation of PrP in vitro …”
Section: Post‐translational Modifications and Artificial Peptides To mentioning
confidence: 99%
“…The incorporation of PEG at different glycosylation sites in PrP only induceds mall changesi n the secondary structure,b ut effectivelyi nhibited the aggregation of PrP in vitro. [26] Apart from glycoproteins, recent efforts in understanding PTMs such as SUMOylation, ubiquitylation, phosphorylation, and lipidation of proteins were also discussed. Champak Chatterjee (University of Washington, USA) presented his laboratory's efforts towards understanding the mechanistic basis of gene regulation by chromatin SUMOylation.…”
Section: Protein Synthesis Beyond the Ribosome: Advances In Chemical mentioning
confidence: 99%